The Effect of Antlion (Myrmeleon sp.) Extract Towards Histopathology Image of Pancreas in Diabetic Mice - Widyatmaka, Muhammad Naufal; Ismail, Akhmad (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Some studies indicated that antlions (Myrmeleon sp.) is traditionally used by many people in Indonesia as a diabetes treatmenter. However. reseach has not been done to find the effect of antlion extract in pancreas, an important organ in diabetes mellitus pathophysiology. Objective: To prove the effect of antlion extract towards histopathological feature of pancreas in diabetic mice.Methods: In the post test only control group design, 25 Swiss mice were divided into five groups. Normal group (Nor-G), Negative control group (Neg-G), and the other 3 groups were intraperitoneally injected with Streptozotocine 200 mg/kg to induce diabetic state. In Neg-G had no antlion treatment, whereas in At-14, At-28, and At-56 were treated with antlion extract at the dose of 14, 28, and 56 mg/kg BW respectively for 24 days. Pancreas then collected and prepared to be examined under microscope with 400x magnification. The score of pancreatic islet injury was determined by assessing structural damage and inflammatory cells infiltration. Kruskal-Wallis and Mann-Whitney were adopted as statistical analysis.Results: Mann-Whitney analysis indicated that the score of pancreatic islets injury in At-56 was significant lower compared to that of Neg-G, p<0.05. The score of pancreatic islets injury in At-56 also significant lower compared to that of At-14 and At-28, p<0.05. In contrary, when compared to that of Nor-G, the pancreatic islets injury in At-56 was not signicantly lower, p>0.05.Conclusion: Antlion extract treatment at the dose of 56 mg/kg BW was capable of reducing pancreatic islet injury in diabetic mice induced by streptozotocine.